1989
DOI: 10.1063/1.101604
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen passivation of electrically active defects in diamond

Abstract: Subjecting natural diamond single crystals to the action of atomic hydrogen in a hydrogen plasma is shown to result in the passivation of interband states in the crystal resulting in a marked reduction in the resistivity to about 105 Ω cm from the expected high resistivity of∼1016 Ω cm. When the hydrogenated crystals are heat treated in a neutral ambient, the hydrogen can be expelled from the crystals, restoring the high resistivity. The behavior of natural diamond crystals, with respect to the effects of hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
91
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(96 citation statements)
references
References 6 publications
4
91
0
Order By: Relevance
“…1 Early Hall measurements confirmed its nature as p-type 2 and subsequent investigations measured an extremely low activation energy. 3,4 High performance devices have been fabricated utilizing this surface conductive layer; [5][6][7][8][9] however its origin is still under debate.…”
Section: Introductionmentioning
confidence: 82%
“…1 Early Hall measurements confirmed its nature as p-type 2 and subsequent investigations measured an extremely low activation energy. 3,4 High performance devices have been fabricated utilizing this surface conductive layer; [5][6][7][8][9] however its origin is still under debate.…”
Section: Introductionmentioning
confidence: 82%
“…[3][4][5][6][7]24 It is also shown that annealing of the films in the inert atmosphere or vacuum decreases the value of 300 by several orders of the magnitude. 24 Here we report the effect of annealing on the 300 of the sheets grown with different deposition conditions. Figure 10͑a͒ shows the I -V characteristics of a typical diamond sheet grown at 20 Torr in different stages of annealing with different annealing temperatures T a .…”
Section: Annealing Studiesmentioning
confidence: 99%
“…On the other hand CVD diamond exhibits a low value of the resistivity ͑on the order of 10 6 ⍀ cm͒. [3][4][5][6][7]24 It is also shown that annealing of the films in the inert atmosphere or vacuum decreases the value of 300 by several orders of the magnitude. 24 Here we report the effect of annealing on the 300 of the sheets grown with different deposition conditions.…”
Section: Annealing Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Landstrass et al proposed that the conduction might be caused by the movements of hydrogen and defects from nonactive sites during the annealing process. 41 Botev et al…”
mentioning
confidence: 99%